Knowledge and context in Tibetan medicine - McGrath, William A. (Leiden ; Boston : Brill, 2019)
Knowledge and Context in Tibetan Medicine is a collection of ten essays in which a team of international scholars describe and interpret Tibetan medical knowledge. With subjects ranging from the relationship between Tibetan and Greco-Arab conceptions of the bodily humors, to the rebranding of Tibetan precious pills for cross-cultural consumption in the People's Republic of China, each chapter explores representations and transformations of medical concepts across different historical, cultural, and/or intellectual contexts. Taken together this volume offers new perspectives on both well-known Tibetan medical texts and previously unstudied sources, blazing new trails and expanding the scope of the academic study of Tibetan medicine. Contributors include: Henk W.A. Blezer, Yang Ga, Tony Chui, Katharina Sabernig, Tawni Tidwell, Tsering Samdrup, Carmen Simioli, William A. McGrath, Susannah Deane and Barbara Gerke.
Chapter 9 Madness and the Spirits: Examining the Role of Spirits in Mental Illness in the Tibetan Communities of DarjeelingChapter 10 Material Presentations and Cultural Drug Translations of Contemporary Tibetan Precious Pills; Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 26, 2025).
eBooks on EBSCOhost
Keywords: Medicine, Tibetan; Medicine, Tibetan -- History; Médecine tibétaine.; Médecine tibétaine -- Histoire; Medicine, Tibetan; History